REGULATION OF INVESTMENT ACTIVITY AS FACTOR OF REGIONAL DEVELOPMENT MANAGEMENT - Natalia P. Molchanova (Advanced Engineering Research, 2011)
Actual problems of the government regulation of the investment activity on the regional level of management are investigated. Availability of the goal-oriented method and ways of developing regional investment policy is considered.